Tren Penelitian Pendidikan Islam pada Fakultas Tarbiyah dan Ilmu Keguruan di IAIN Samarinda - Khojir Khojir; Dian Wahid H (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2017)
This research is directed to evaluate the research topics done by the students of teacher training and education faculty of IAIN Samarinda from 2014-2016 which can be used as the references to develop the research quality of IAIN Samarinda. This research was done by applying the quantitative bibliometric. The data was collected by using the documentation of the thesis abstracts of the students of teacher training and education faculty of IAIN Samarinda. The data was analysed by using co-word analysis. The results show that the dominant topics focused by the PAI students to write the thesis from 2014-2016 were about the cognitive, affective, and psycomotoric learning aspects. The topic trend of the Educational management students to write the thesis from 2014-2016 were about the educators and non-educators management, whereas the topic trend of the English department students to write the thesis from 2014-2016 were about the speaking ability of the English learners. The dominant research approaches used by the all three study programs were quantitative research. The suggestions are given related to the findings are: 1) It needs to enrich and enlarge the topics research should be done by the students of teacher training and education faculty of IAIN Samarinda and 2) The students need to learn more about the research methods to improve the accuracy and the validity of the research done by the students.